Realidades do mundo do trabalho de uma equipa comunitária de suporte em cuidados paliativos e as suas implicações nos cuidados aos doentes em trajetórias de fim de vida - Mestre, Tatiana Filipa Silva; Silva, Carlos Alberto da (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
Discovering the readings of health professionals on home care practices for patients at the end of their life, through a sociological prism, is one way to better understanding the nature of palliative care. In this article, we have explored the voice of healthcare professionals from a Community Palliative Care Support Team (ECSCP), analyzing the implicit textuality of their discourse and perspectives on the nature of palliative, curative and preventive work, challenges of work on end of life process, logic of communication and translation to solve problems at work as part of the patient's end of life trajectory. This article has been prepared on the basis of preliminary data analysis collected between 2019 and 2020, as part of the project funded by the Foundation for Science and Technology (FCT), entitled ETIC (End-of-Life Trajectories In Care) - Managing end-of-life trajectories in palliative care: a study on the work of healthcare professionals.